Dom Quixote em cordel de J. Borges: uma adaptação brasileira de Cervantes - Carvalho, Erivelto Da Rocha (Diálogos Latinoamericanos, 2013)
Dom Quixote em cordel (2005), by J. Borges, is an adaptation of Cervantes’s masterpiece to a Brazilian scenery; the renowned folk artist represents a number of scenes from Cervantes’s novel proposing the identification of its characters with some typical individuals from the Northeastern backlands, especially those related to banditry. The objective of this article is to conduct a brief analysis of Borges’s poem, in which it is given special attention to the identification between the imaginary territories of La Mancha and Brazilian Northeast. Under this perspective, historical characters, such as the highwaymen Lampião and Maria Bonita, play an important role as representatives of Brazilian irredentism. They are considered, in the work of Borges, emblems of peculiar aesthetics highwaymen.